PATH-40. INTRAGENIC DMD DELETIONS ARE THE MOST COMMON RECURRENT GENOMIC ALTERATIONS IN ESTHESIONEUROBLASTOMA. (9th November 2020) - Juratli, Tareq; Nayyar, Naema; Young, Michael; Subramanian, Megha; Brastianos, Priscilla; Lin, Derrick
Abstract: INTRODUCTION: Esthesioneuroblastoma (ENB) is a rare, malignant neuroectodermal tumor of the olfactory epithelium. To date, a few recurrent genetic alterations have been identified in ENB. Here, we sought to examine the genomic signature on a series of clinically well-characterized aggressive ENB samples. METHODS: We performed whole-exome sequencing in a cohort of 26 ENB samples from 12 patients, containing 11 matched primary-metastatic samples. Additionally, targeted sequencing was carried out in all samples to determine TERT promoter hotspot mutations. Furthermore, we performed immunohistochemistry (IHC) using an antibody that recognizes the dystrophin central rod domain in all available specimens. RESULTS: Our cohort consisted of 9 male and 3 female patients with a median age of 66 years at first diagnosis (4- 77 years). One patient was staged Kadish B at the time of diagnosis and eleven were staged Kadish C. The median overall survival was 3.85 years (0.3 – 16 years). Consistent with previous findings, each tumor exhibited a different mutational signature and the mutational landscape appears to be predominantly driven by copy number variations. Interestingly, we detected intragenic deletions in dystrophin ( DMD ) as the most common and consistent alteration in ENB patients (in 11 of 12 patients, 91.6%). DMD deletions, when identified within the primary ENB, were preserved in all subsequent metastatic lesions. Moreover, DMD deletions where concurrently identified in three cases with multiple metastases. IHC revealed the concurrent loss of dystrophin expression, the protein encoded by DMD, in all cases with DMD deletions. Otherwise, no other recurrent genomic findings were detected, including TERT promoter mutations. CONCLUSIONS: Our findings validate previously described DMD deletions as the most common recurrent genomic alteration in primary ENB. Furthermore, our data demonstrate that DMD deletions were perpetuated in subsequent metastatic lesions, and when identified in any metastasis, were present in other metastases from the same patient.